The South Korea Halloween Crush in CNN News: A NetMiner Analysis - Kang, Namkil (Advances in Social Sciences Research Journal, 2023)
The ultimate goal of this paper is to analyze 40 pieces of CNN news broadcasted from 20th 10 2022 to 17th 12 2022 regarding the South Korea Halloween crush. It must be stressed that one word has the highest frequency (443 tokens) and the highest proportion (0.394) in 40 pieces of CNN news. When it comes to the word cloud of 40 pieces of CNN news, the word person is the biggest in size, which in turn suggests that it is the most significant one. With respect to topics occurred in the CNN news, it is noteworthy that topic 2 was the most occurred one, followed by topic 7, topic 6, and topic 1. It must be emphasized, on the other hand, that the probability for the word Seoul to be the first keyword is the highest (0.136). More importantly, it should be pointed out that the word person was the most occurred one in 40 pieces of CNN news, followed by the word crowd, the word Seoul, the word police, the word Itaewon, and the word crush, in that order. As for the links among the relevant keywords occurred in 40 pieces of CNN news, the keywords accident, call, official, response, report, and government are directly linked to the word emergency. These links seem to show that people in danger requested for rescue.